Analisis dan Perancangan Enterprise Architecture Menggunakan TOGAF ADM di Unit Koleksi Penagihan - Farouq Zulfikar Fahlevi; Fitriyana Dewi; Dhata Praditya (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
In the era of rapid technological advancement, it is crucial for companies to optimize their information systems to support performance and success. Companies need to undertake comprehensive and integrated information system planning to prevent disjointed systems within an enterprise, which could potentially hinder the company's access to necessary information. Enterprise Architecture (EA) emerges as a holistic approach to designing and integrating systems within a company with the aim of providing a roadmap to achieve the desired state from the current condition. EA focuses not only on Information Technology (IT) strategy but also integrates IT strategy with the company's vision and mission. This integration is intended to optimize opportunities and manage change initiatives that can generate added value. In its design, EA requires a framework to align the business with forthcoming technology. The TOGAF ADM framework has been recognized as a useful method that presents a structured and comprehensive approach to developing EA. ADM guides EA practitioners through a series of well-defined stages, from planning to implementation. In this context, this research aims to design an EA that can enhance services in the Collections and Billing function. By optimizing workflows, reducing data duplication, and enhancing billing visibility, it is expected that EA can yield a more efficient and accurate billing collection process. Consequently, companies can achieve better adaptability, security, and sustainability when facing dynamic business changes